Understanding ICT implementation effectiveness in mathematics education: A systematic review - Muhammad Shehryar Rao; Dyana Wijayanti; Ousman Bah (Universitas Sarjanawiyata Tamansiswa, 2025)
The application of Information and Communication Technology (ICT) in mathematics education is indeed transformative, but it produces uneven results, with a significant gap between student engagement levels and their mathematical success. This review aims to explain under which contextual, pedagogical, and institutional conditions ICT integration becomes genuinely effective. This systematic review of 49 empirical studies conducted between 2015 and 2024 critically analyzes the dominant Technological Pedagogical Content Knowledge (TPACK) framework, highlighting its weaknesses in explaining why similar applications produce different results in diverse cultural and socioeconomic environments. Our analysis reveals a crucial “engagement-achievement” paradox, where 84% of studies show increased engagement; however, only 64% reveal corresponding improvements in achievement. These results emphasize that effectiveness is not solely influenced by the level of technological sophistication, but through complex interactions involving depth of implementation, pedagogical appropriateness, cultural relevance, and institutional support. We advocate for a successful framework that combines these multifaceted elements, with a focus on equity and critical pedagogy to ensure that technology functions as a transformative force rather than one that reinforces existing disparities in mathematics education. This review offers evidence-based recommendations for moving beyond uniform strategies toward context-aware and sustainable technology integration. This study contributes theoretically by extending the TPACK discourse with a multidimensional, context-sensitive perspective that integrates equity and critical pedagogy into ICT effectiveness analysis.